Computational analysis of fire and people evacuation for different positions of burning vehicles in a road tunnel with emergency exits. Issue 1 (1st January 2018) - Caliendo, Ciro; Ciambelli, Paolo; Guglielmo, Maria Luisa Deonal; Meo, Maria Grazia; Russo, Paola
Abstract: The paper shows the findings of fire simulation for various types of vehicles located in different longitudinal positions within a road tunnel. This is an issue that researchers have little investigated over time and so very few studies are available in the literature. The corresponding environmental conditions (expressed in terms of temperature, radiant heat flux, visibility, and CO concentration) along the people evacuation path are also presented, while the associated safety conditions with and without emergency exits are estimated. Computational Fluid Dynamic (CFD) modelling showed for the burning vehicle, which was located half way along the tunnel, higher temperatures compared to the position at one-fourth of the tunnel length (L). However, the environmental conditions along the escape route were found to be worse when the fire source was at 1/4 L compared to that at 1/2 L, since the evacuation time was higher due to the longer distance to the exit portal. Irritant smoke compared to non-irritant smoke caused a greater negative effect on the safety of the people. No significant difference between a curved tunnel compared to a straight one was found, while with 2% longitudinal slope, inducing the chimney effect, less severe conditions on people safety along the evacuation path were found. The advantages of providing the tunnel with emergency exits were also shown, and their optimal distance was identified. The analysis developed in this paper applied to different positions of various burning vehicles, and combinations of traffic and geometry set out to increase our knowledge on safety in road tunnels.